2004
DOI: 10.1007/s00406-004-0540-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between exploratory eye movements and brain morphology in schizophrenia spectrum patients

Abstract: The exploratory eye movements of schizophrenia patients and their relatives have been shown to differ from those of patients without schizophrenia and healthy controls. However the mechanism of exploratory eye movement disturbances in schizophrenia patients remains elusive. We investigated the relationship between the exploratory eye movements and brain morphology in 39 schizophrenia spectrum patients. Voxel-based morphometric analysis on three-dimensional magnetic resonance imaging was conducted by means of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…In 2 studies, the scanpaths of individuals with schizophrenia receiving neuroleptics did not differ from those of never-medicated patients (cross sectional design, 48 longitudinal design 41,48 ). Other researchers have found no influence of medication type (typical v. atypical neuroleptics 51,62 ) or duration 74 on scanpath variables. Evidence that antipsychotic medications may reduce abnormalities in viewing behaviour also suggests that restricted scanning is not a consequence of neuroleptic treatment.…”
Section: Association With Other Clinical Featuresmentioning
confidence: 87%
See 2 more Smart Citations
“…In 2 studies, the scanpaths of individuals with schizophrenia receiving neuroleptics did not differ from those of never-medicated patients (cross sectional design, 48 longitudinal design 41,48 ). Other researchers have found no influence of medication type (typical v. atypical neuroleptics 51,62 ) or duration 74 on scanpath variables. Evidence that antipsychotic medications may reduce abnormalities in viewing behaviour also suggests that restricted scanning is not a consequence of neuroleptic treatment.…”
Section: Association With Other Clinical Featuresmentioning
confidence: 87%
“…patterns in individuals with schizophrenia and an unaffected control viewer. A central role of frontal lobe pathologies in abnormal scanning is supported by neuroimaging findings, 73,74 similarities between scanpaths of patients with schizophrenia and individuals with frontal lobe lesions, 54,75,76 correlations with neuropsychological performance 56 and an association with negative symptoms, which in turn are linked with prefrontal dysfunction. 77 Scanpath abnormalities may represent an epiphenomenon of a more basic dysfunction in oculomotor control that is assessed by more established putative trait markers in individuals with schizophrenia.…”
Section: Scanpaths As Potential Trait Markers In Individuals With Schmentioning
confidence: 93%
See 1 more Smart Citation
“…It has been suggested that in schizophrenic patients with cortical atrophy [28], modulation processing may not be suitable because it could have widespread effects on voxel signal intensities and may result in less consistent spatial localization of gray matter volume differences from sample to sample [29], [30]. Besides, the analysis of unmodulated data in schizophrenia is fertile [29], [31] and has been successfully conducted to explore the relationship between EEM and brain morphology in schizophrenia [20]. Thus we only used unmodulated data for GMD analysis in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…However, studies on exploring the underlying neuropathological mechanism of the EEM dysfunction in schizophrenia were relatively sparse. A pioneer study exploring the relationship between the EEM and brain morphology has presented that RSS was significantly related to gray matter density (GMD) in the right frontal eye field (rFEF) and right inferior frontal region in schizophrenia-spectrum patients [20]. The study increased the understanding of EEM abnormalities.…”
Section: Introductionmentioning
confidence: 99%